Dynamic process of single water droplet impinging burning liquid pool existing on a water layer - Xu, Mingjun (2024)
This paper presents the mechanism of flame expansion during the process of a single water droplet impacting a thin diesel pool fire existing on a water layer. The mechanism of flame expansion is deeply analyzed. Splashing is the main factor causing flame expansion. For the quantitative analysis, it is found that the water droplet’s diameter and falling height have significant effects on the intensity of flame expansion, and the quantitative relationships among the dimensionless intensity of flame expansion, water droplet diameter, and falling height are provided in this study. A comprehensive formula, i.e., (Hmax - Ho)/Dpool = 0.00294We - 0.57, in the combination of the dimensionless intensity of flame expansion i.e., (Hmax - Ho)/Dpool, droplet diameter d and falling height h, is provided to predict the intensity of flame expansion, which is of great importance to quantify the intensity of flame expansion. Additionally, the instantaneous flame area is calculated to quantify the intensity of flame expansion. The expansion intensity of the flame area (Am - A0)/A0 increases with the droplet diameter d and falling height h.